Enhancing School Brand Performance Through Internal Branding Strategies : A Case Study of LPI Al-Haromain Surabaya - Christina, Ani; Muryati, Muryati; Mas’ud, Muchlis H. (Jurnal Manajemen, 2025)
This study investigates the role of internal branding in enhancing school brand performance, mediated by brand commitment and brand loyalty, within Islamic educational institutions. A quantitative approach was applied using data from 92 educators and staff members at five school units managed by LPI Al-Haromain Surabaya. The population of this study consists of all educators and staff members of LPI Al-Haromain Surabaya, totaling fewer than 100 individuals. Therefore, saturated sampling was applied, in which all population members were included as respondents. Data analysis was conducted through Structural Equation Modeling using the PLS-SEM method. The results indicate that internal branding significantly boosts brand performance and brand commitment, while its impact on brand loyalty does not lead to improved performance. Brand commitment acts as a key mediator, whereas brand loyalty lacks significant influence without active engagement. Grounded in the theoretical frameworks of Resource-Based View (RBV), Social Exchange Theory, and Brand Equity Theory, the study highlights internal branding as a strategic driver of employee alignment with brand values. The study contributes to the literature by addressing a population gap, as most internal branding studies have focused on industry and higher education contexts. It further introduces the concept of educators as internal brand ambassadors and "teachers as school ambassadors," affirming their role in embodying and delivering brand values in daily interactions with students and parents.